2009
DOI: 10.1007/s12665-009-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of coal mining subsidence on the surface landscape in Longkou city, Shandong Province of China

Abstract: Coal mining subsidence is a common human geological disaster that was particularly conspicuous in China. It seriously restricts the sustainable development of mining areas, and it not only damages land resources but also triggers a series of ecological and environmental problems that may result in social and economic issues. This report studied the coal mining subsidence area of Longkou in Shandong province and uses digital elevation data (DEM) of the mining area before subsidence in 1978 as the baseline eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 4 publications
0
34
0
Order By: Relevance
“…Recent studies have analyzed ground-subsidence hazards using the results of geological and geotechnical investigations, as well as probability, statistics, fuzzy algebra, and artificial neural network (ANN) models in geographic information system (GIS) applications (Ambro zi c and Turk, 2003;Kim et al, 2006;Esaki et al, 2008;Turer et al, 2008;Kim et al, 2009;Mancini et al, 2009;Quanyuan et al, 2009;Choi et al, 2010;Lee et al, 2010;Lee, 2010, 2011;. Some studies have assessed and identified areas with high subsidence risk.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have analyzed ground-subsidence hazards using the results of geological and geotechnical investigations, as well as probability, statistics, fuzzy algebra, and artificial neural network (ANN) models in geographic information system (GIS) applications (Ambro zi c and Turk, 2003;Kim et al, 2006;Esaki et al, 2008;Turer et al, 2008;Kim et al, 2009;Mancini et al, 2009;Quanyuan et al, 2009;Choi et al, 2010;Lee et al, 2010;Lee, 2010, 2011;. Some studies have assessed and identified areas with high subsidence risk.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ground subsidence hazards have been analyzed using results of geological and geotechnical investigations and probability, statistic, fuzzy algebra and artificial neural network models in tandem with geographic information system (GIS) application (Ambrožič and Turk 2003;Choi et al 2010;Kim et al 2006Kim et al , 2009Lee et al 2010;Oh and Lee 2010;Quanyuan et al 2009;Turer et al 2008). Some ground subsidence hazard assessments that include the identification of areas with a high subsidence risk have been published.…”
Section: Introductionmentioning
confidence: 99%
“…In the Son‐Mahanadi Master Coal Basin in western India, depressions ranging from 2 to 26 m have also been found (Singh, ). In the vicinity of Longkou city in the Shandong Province of China, areas that subsided by 3 to 5 m account for the greatest share of land, but a steady increase in the amount of land affected by mining has been observed (Quanyuan et al ., ). In 2004, subsidence affected slightly over 12 km 2 of land of which nearly 30% was in areas that had subsided by more than 5 m (Quanyuan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the vicinity of Longkou city in the Shandong Province of China, areas that subsided by 3 to 5 m account for the greatest share of land, but a steady increase in the amount of land affected by mining has been observed (Quanyuan et al ., ). In 2004, subsidence affected slightly over 12 km 2 of land of which nearly 30% was in areas that had subsided by more than 5 m (Quanyuan et al ., ). A similar scale of subsidence due to mining is observed by Djamaluddin et al .…”
Section: Discussionmentioning
confidence: 97%